Peran Kepercayaan sebagai Variabel Mediasi antara Konten Media Sosial dan Engagement terhadap Minat Mendaftar di Institut Informatika dan Bisnis Darmajaya - Muhammad Saputra; Novita Sari; Ketut Artaye; Arif Nur Fitriyanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the role of trust as a mediating variable between social media content and Engagement on the intention to enroll at Institut Informatika dan Bisnis Darmajaya. The research adopts a quantitative approach with an explanatory research design to test the causal relationships among the variables. The data used in this study are primary data collected directly from respondents. The population of this research consists of potential students, including senior high school and vocational high school students in their final year (Grade XII), as well as employees who have seen, followed, or are familiar with the official social media content of Institut Informatika dan Bisnis Darmajaya. The sampling technique employed is purposive sampling, with criteria that respondents must be at least 16 years old and have interacted with or followed at least one of Darmajaya’s official social media accounts (Instagram, TikTok, YouTube, or Facebook). The total sample size is 180 respondents, determined based on Hair’s formula. Data analysis was conducted using Structural Equation Modeling (SEM) based on the Partial Least Squares (PLS) method with the aid of SmartPLS version 4.0 software. The findings reveal that social media content has a significant effect on trust, and Engagement also has a significant effect on trust. Moreover, social media content significantly affects the intention to enroll, whereas Engagement does not have a significant direct effect on the intention to enroll. Furthermore, trust significantly.